Proceedings of the 5th International Conference on Conversational User Interfaces 2023
DOI: 10.1145/3571884.3604313
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Large Language Models for Cognitive Assistants in Factories

Abstract: As agile manufacturing expands and workforce mobility increases, the importance of efficient knowledge transfer among factory workers grows. Cognitive Assistants (CAs) with Large Language Models (LLMs), like GPT-3.5, can bridge knowledge gaps and improve worker performance in manufacturing settings. This study investigates the opportunities, risks, and user acceptance of LLM-powered CAs in two factory contexts: textile and detergent production. Several opportunities and risks are identified through a literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Xia et al ( 2023 ) demonstrated how using in-context learning and injecting task-specific knowledge into an LLM can streamline intelligent planning and control of production processes. Kernan Freire et al ( 2023a ) built a proof of concept for bridging knowledge gaps among workers by utilizing domain-specific texts and knowledge graphs. Wang X. et al ( 2023 ) conducted a systematic test of ChatGPT's responses to 100 questions from course materials and industrial documents.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al ( 2023 ) demonstrated how using in-context learning and injecting task-specific knowledge into an LLM can streamline intelligent planning and control of production processes. Kernan Freire et al ( 2023a ) built a proof of concept for bridging knowledge gaps among workers by utilizing domain-specific texts and knowledge graphs. Wang X. et al ( 2023 ) conducted a systematic test of ChatGPT's responses to 100 questions from course materials and industrial documents.…”
Section: Introductionmentioning
confidence: 99%